Theoretical Aspects of Regional Competitiveness Measurement - Simanavičienė, Žaneta; Bruneckienė, Jurgita; Šimberova, Iveta (Ekonomika, 2007)
The necessity of proper analysis of the regional competitiveness concept brings the recognition. that the drivers of national competitiveness have become more local and the regions increasingly becoming the engines of the global economy, as the globalization blurs national borders. Furthermore, the regionalization of public policies moves the economic coordination and steering functions from the national state down to regional level.The topic of regional competitiveness is relevant in Lithuania also. Despite the fact, that the juristic base of regional policy is developed, it is still in conceptual stage. The developing of regional policy bristles with difficulties. therefore the efficiency of the policy is reducing and the economic and social differences among Lithuania’s regions are increasing. The concept of regional policy and regional competitiveness become a subject to a great interest, especially implementing Eu rope Union financed projects in order to reduce the differences of development and increase the competitiveness of Lithuania’s regions.The academic debate about regional competitiveness has been going on for several years, fuelled by critiques, but no consensus has arrived yet. There’s still no theoretical perspective that captures the full complexity of regional competitiveness and assessment of it. Every academic creates his own regional competitiveness model and theoretically and empirically justify. As the concept of national competitiveness was analyzing by academics fur a long time and many models of national competitiveness are already formed, the theoretical analysis of these models in the context of regional competitiveness measurement would improve understanding of regional competitiveness and identify the methodological principals and suggestions of tbe assessment of regional competitiveness.The aim of the research is to analyze the models of national competitiveness in the context of regional competitiveness and identify the methodological principal, and suggestions of regional competitiveness measurement.Object .r the re.eareh is the abilities of national competitiveness models in the measurement the regional competitiveness.Methods of the research - analysis and synthesis of the scientific literature, logical and comparative analysis.The theoretical analysis of national competitiveness models shows, that M. Porter “National Diamond” model, D. S. Cho “Nine factors” model, A. M. Rugman, J. R. D’Cruz and A. Verbeke “Double Diamond” model, M. Porter and D. S. Cho and H. C. Moon “Competitiveness Stage,” models are the most comprehensive in the theoretical and empirical viewpoint.The authors of article accept M. Porter “National Diamond” model as methodological base of modeling national competitiveness but misdoubt its ability in the measurement of regional competitiveness.The authors of article accept A. M. Rugman, J. R. D’Cruz and A. Verbeke “Double Diamond” model a, methodological base of analyzing and modeling regional competitiveness. It’s still not clear, which diamond would reflect regional, national and international competitiveness, so this model should be adapted to the specially of regions.The analysis of D. S. Cho “Nine factors” model shows that it is insufficient systemically justified. The lack of empirical analysis of this model misdoubts its ability in the measurement of national and regional competitiveness.The theoretical analysis of M. Porter and D. S. Cho and H. C. Moon “Competitiveness Stages” models define the importance of comparing the competitiveness among economically and socially similar regions.The national competitiveness models, analyzed in the article, are formed to analyze bigger or smaller counties, but not regions. The specific of regions do not allow to adapt directly these models to the measurement of regions competitiveness, but the methodological principals should be used in the process of me.suring regional competitiveness.The authors of the article suggest that the assessment of regional competitiveness should be based of these methodological principals:clearly identify the factors of regional competitiveness and the relation among each other and the impact to overall competitiveness;to use the indicators, that is not dependent on the shift of economic cycle;to group the regions by one criteria and compare among each other similar regions;In order to measure the regional competitiveness, the internal and external factors of regional competitiveness should be identified, the specialty of regions should be defined and the theoretically and logically justified model of competitiveness should be created.